Princípio da inadmissibilidade das provas obtidas por meios ilícitos - Wenzel, Leiliane Freitas Almeida (2007)
The present dissertation has as a main goal to discuss the principle of inadmissibility of proofs which are obtained through illicit means in the process which has assumed a new dimension in the Brazilian system with the Constitution of the Federal Republic of Brazil from 1988, being it inserted in the Title of the Rights and Fundamental Guarantees. The research was eminently bibliographic and jurisprudential. The work analyzes the right to proof and its Legal Constitutional protection. It Approaches the rights and applicable Guarantees foreseen in the constitution of 1988, applicable to the proof. The principle of inadmissibility of the proofs obtained in the process through illicit means is analyzed under a constitutional prism. It adduces that the proofs which are obtained through illicit means break the rule of the material right essentially existing in the constitution of 1988 as well as in infra-constitutional laws. It explains the theory of the Fruit of the Poisoned Tree, even presenting some collective judgment of the Federal Supreme Court. It also approaches questioning related to the principle of proportionality and reasonability involving the proof obtained illicitly, questioning weather the mentioned proof can be used in favor of the defendant or in behalf of the society. It deals with the theory of the Fortuitous or casual discovery of proofs. It also brings reflections concerning the Law nº 9.296/96 and to the principle of the inadmissibility of proofs obtained through illicit means.